Toll-like receptor-7/8 agonist kill Leishmania amazonensis by acting as pro-oxidant and pro-inflammatory agent. (3rd May 2021) - Kaushik, Deepender; Granato, Juliana T; Macedo, Gilson C; Dib, Paula R B; Piplani, Sakshi; Fung, Johnson; da Silva, Adilson D; Coimbra, Elaine S; Petrovsky, Nikolai; Salunke, Deepak B
Abstract: Objectives: Evaluation of the anti-Leishmanial activity of imidazoquinoline-based TLR7/8 agonists. Methods: TLR7/8-active imidazoquinolines (2 and 3 ) were synthesized and assessed for activity against Leishmania amazonensis -intracellular amastigotes using mouse peritoneal macrophages. The production of reactive oxygen species (ROS), nitric oxide (NO) and cytokines was determined in infected and non-infected macrophages. Key findings: The imidazoquinolines, 2 and 3, were primarily agonists of TLR7 with compound 3 also showing modest TLR8 activity. Docking studies showed them to occupy the same binding pocket on TLR7 and 8 as the known agonists, imiquimod and resiquimod. Compounds 2 and 3 inhibited the growth of L. amazonensis -intracellular amastigotes with the most potent compound (3, IC50 = 5.93 µM) having an IC50 value close to miltefosine (IC50 = 4.05 µM), a known anti-Leishmanial drug. Compound 3 induced macrophages to produce ROS, NO and inflammatory cytokines that likely explain the anti-Leishmanial effects. Conclusions: This study shows that activating TLR7 using compounds 2 or 3 induces anti-Leishmanial activity associated with induction of free radicals and inflammatory cytokines able to kill the parasites. While 2 and 3 had a very narrow cytotoxicity window for macrophages, this identifies the possibility to further develop this chemical scaffold to less cytotoxic TLR7/8 agonist for potential use as anti-Leishmanial drug. Graphical Abstract: